Synthesis and characterization of crystalline polymeric carbonic acid (H2CO3) with s p 3-hybridized carbon at elevated pressures - Dominik Spahr; Lkhamsuren Bayarjargal; Lukas Brüning; Valentin Kovalev; Lena M. Wedek; Maxim Bykov; Victor Milman; Nico Giordano; Björn Winkler; Elena Bykova (Communications Chemistry)
Abstract The existence of polymeric carbonic acid (H2CO3) at elevated pressures has been predicted, but has not been investigated experimentally. Here, polymeric carbonic acid containing s p 3-hybridized carbon was synthesized and characterized at  ≈40 GPa. H2CO3 single crystals were obtained by laser-heating a H2O + CO2 mixture in a diamond anvil cell. The orthorhombic crystal structure (C m c21 with Z = 4) was refined from synchrotron single crystal X-ray diffraction data and is in agreement with a structural model predicted earlier. The crystal structure of H2CO3-C m c21 is characterized by $${[{{\rm{CO}}}_{4}]}^{4-}$$ [ CO 4 ] 4 − building blocks which are connected via corner sharing, forming chains along the c-axis. The combination of single crystal X-ray data with experimental Raman spectroscopy and DFT-calculations confirms that the structural model of H2CO3-C m c21 is appropriate. The synthesis condition of polymeric carbonic acid points towards its potential existence in ice giants including the ones present in our solar system.